Pedidikan Akhlak Di Madrasah Ibtidaiyah Miftahul Ulum Bendung Jetis Mojokerto - Muhammad Romadlon Habibullah; Hamidatun Nihayah; Habibatul Imamah (Pendidikan Agama Islam, 2020)
Moral education is the spirit of Islamic religious education and achieving a perfect morality is the real goal of education. Moral education is important for humankind the importance of morals is not only in the life of the individual but also in living in the family and society, even in the life of dancing. Morals are the essence of life and make the difference between humans and animals. â€œAkhlakâ€ is conscious guidance or leadership by educators of the educated is physical and spiritual development towards the formation of praiseworthy morals. The concept of moral education in Madrasah Ibtidaiyah Miftahul Ulum not stated directly in the vision and mission of the madrasah. However, moral education values â€‹â€‹are, in the student code of ethics, for exemplary methods, habituation, lectures, and stories, as well as reward and punishment, implementation of moral education at MTs Madinatul Ulum Baureno Bojonegoro. They are teaching human resources, complete regulatory tools, hidden curriculum, religious culture facilities, and infrastructure that are sufficient to support moral education activities. Meanwhile, the inhibiting faktors for moral education at MTs Madinatul Ulum Baureno Bojonegoro consisted of internal faktors; Inconsistent and sustainable enforcement of rules, Limited time in Madrasa. External faktors; Family environment, community environment.